Creative Destruction and Library Services. - Alvin Hutchinson (Issues in Science and Technology Librarianship)
The article describes how the Internet has pushed libraries to adopt a self-service model. With the licensing of online journal content, finding and retrieving articles no longer requires a visit to the library or the interlibrary loan office. Moreover, with reduced library visitorship due to more desirable digital delivery services, science librarians have to change their way of operating and to develop more direct-to-reader services.